The study on extraction process and analysis of components in essential oils of black pepper (Piper nigrum L.) seeds harvested in Gia Lai Province, Vietnam - Tran, Thien Hien; Ha, L. K.; Nguyen, D. C.; Dao, T. P.; Nhan, L. T. H; Nguyen, Dai Hai; Nguyen, Trinh Duy; Vo, Dai-Viet N.; Tran, Q. T.; Bach, Long Giang (MDPI AG, 2019)
Black pepper (Piper nigrum L.) is a tropical crop with extensive medicinal potential in ethnomedicine and nutraceutical applications. The essential oil of black pepper finds wide applications in inhabitation of respiratory infections and soothing of muscular pains due to its warming and energizing property. The pungent bioactive piperine is responsible for this function, and therefore, efficient technology is required for an optimal extraction process of this compound. In the present article, we have developed a procedure for extracting black pepper essential oil from Vietnam, optimizing conditions that affect the extraction process. The effect of process parameters, namely material size, preservation method, the concentration of sodium chloride, the concentration of soak time, the ratio of material to water, temperature extraction, time extraction on the extraction yield, and relative efficiency were investigated. Results demonstrated that 20 g of black pepper milled with a mesh size of 160 obtained 0.48 g of essential oil (2.4%) at a raw material to water ratio of 1/21 (g/mL) at 150 °C in a time of 5.2 h. GC-MS (Gas chromatography–mass spectrometry) spectra showed that 3-carene (29.21%), D-limonene (20.94%), caryophyllene (15.05%), and β-pinene (9.77%) were present as major components. These results suggested that the essential oil extracted from Vietnamese black pepper is applicable in the manufacturing processes of insecticides and air deodorizers.